2000
DOI: 10.1016/s1074-7613(00)00015-7
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Acquisition of Inhibitory Ly49 Receptors on Developing NK Cells Is Successively Restricted and Regulated by Stromal Class I MHC

Abstract: We report an in vitro stroma-dependent system for the clonal growth and differentiation of natural killer (NK) cells from lymphoid-restricted bone marrow progenitors or bone marrow NK1.1+ cells. Strikingly, the potential to initiate expression of specific Ly49 receptors becomes increasingly restricted as NK cells develop. Moreover, when NK cells express a Ly49 receptor specific for stromal cell class I MHC, they are less likely to initiate expression of another Ly49 receptor in the clonal culture system. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
100
1
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 31 publications
12
100
1
1
Order By: Relevance
“…In bone marrow, it has been reported that CD146 1 subendothelial stromal cells are responsible for the ectopic reconstitution of a hematopoietic microenvironment [16]. It is known that bone marrow stromal cells do play a role in NK cell maturation [31] and we found CD146 expression in some NK cells from mouse bone marrow. Thus, if CD146 homophilic interactions occur in vivo, the adhesive properties of CD146 could influence NK cell maturation.…”
mentioning
confidence: 48%
“…In bone marrow, it has been reported that CD146 1 subendothelial stromal cells are responsible for the ectopic reconstitution of a hematopoietic microenvironment [16]. It is known that bone marrow stromal cells do play a role in NK cell maturation [31] and we found CD146 expression in some NK cells from mouse bone marrow. Thus, if CD146 homophilic interactions occur in vivo, the adhesive properties of CD146 could influence NK cell maturation.…”
mentioning
confidence: 48%
“…Data presented to date are consistent with both of these models. Recent data from two in vitro cell culture systems suggest that NK cells begin to express different Ly49 receptors at different times during their development, although the order of receptor expression differed between the two systems (49,50). The sequential and selection models make different predictions about how expression of a single Ly49 receptor on all NK cells would alter the repertoire development.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro data suggest that there may be a time element that needs to be considered (49,50). During NK cell differentiation, there may be a discrete stage in which Ly49 receptor genes can be activated.…”
Section: Discussionmentioning
confidence: 99%
“…An orderly acquisition of NKR has been described on Leukemia mouse NK cells. [41][42] It is thus possible that shaping of the NKR repertoire is also sequential in humans, with CD158a/h being expressed later in the course of NK cell maturation. Nevertheless, the present phenotypic characterization supports the fact that NK cells present in hematopoietic grafts, and thus infused in patients during the course of allogeneic transplantation, are equipped with multiple NKR, and are therefore capable of interactions with MHC class I molecules.…”
Section: Figurementioning
confidence: 99%